Expressive Speech Acts of Buyer Comments on the Jennskin Naturals Officials Shopee Account - Afiyah Masruri; Rika Ningsih (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This research was motivated by the many expressive speech acts contained in buyers' comments on the Shopee Jennskin Naturals Officials account. Buyers' expressive speech acts have an important position and greatly influence the psychology of other buyers regarding their satisfaction with the online shopping experience. The problem of this research is how to express the expressive speech acts of buyers' comments on the Shopee Jennskin Naturals Officials account. The aim of this research is to explore and elaborate on the expressive speech acts of buyers' comments on the Shopee Jennskin Naturals Officials account. The theory used in this research is the theory of expressive speech acts proposed by Searle. This research uses a qualitative approach with the content analysis method. The data in this research are expressive speech contained in buyers' comments on the Jennskin Naturals Official shopee account. The data source for this research is the speech in the comments of buyers of the Jennskin Naturals Official shopee account which were spoken by buyers of deodorant products with screenshots. Data collection techniques use documentation and notes. Data analysis techniques in this research are data transcription, classification or grouping data, description stage or analyzing data and concluding data. The results of this research found a total of 201 data of expressive speech, there were 63 data of thanks, 14 congratulated, blamed 20 and praised 104. Of the expressive speech found, the most dominant was the expressive speech of praise. The usefulness of this study in education can be a guide for teachers, students and other readers in expressing appropriate speech to interlocutors in their daily lives